Application of IEEE 802.1X in HiperLAN type 2 Chalmers - Kelati, Amleset (My University, 2001)
The research within Information Technology has been subject to a tremendous speed-up in the latest years, mainly due to the reduced prices of the related technology and, consequently, to a strongly increased interest of the users. This causes a positive feedback loop, since many companies decide to invest more money in such area, reducing further the prices and accelerating this process. One of the major issues in this big race has been the concept “Be connected always and everywhere”, which translated in an increased development of public networks on one side and in a further growth of big corporation networks on the other side. The common factors of these big areas are mobility, which implies wireless networks, and availability of services, which also means access to more or less important information. Increased size, mobility and availability of services on networks that become bigger and bigger increases tremendously the importance of data-security. Trust, authentication, and authorization have become vital key words within the design of big, mobile networks. IEEE 802.1X, also known as “Port Based Network Access Control” is a means for providing authentication and authorization for big networks that offer the possibility to many devices to attach to them, making their services available. This master thesis work, carried out at Ericsson Enterprise AB, Wireless LAN Systems in Sundbyberg (Sweden), had as a primary objective to study the authentication and authorization standard IEEE 802.1X (Draft version 11, released March 27th 2001) and its integration in HIPERLAN type 2 (HIPERLAN/2), which is a standard for wireless LAN. The project has been accomplished for the Department of Signals and Systems at the Chalmers University of Technology in Göteborg, Sweden. The goals of the thesis work were to analyze the current version of the standards and other related protocols in order to gain competence in the area of the study how IEEE 802.1x could be integrated in HIPERLAN/2 based network. In this work we propose a solution for the implementations problem and design, develop and test a basic prototype. The result shows that IEEE 802.1x can be deployed within a wireless network based on HIPERLAN/2 by adapting certain features of the two standards and by adopting certain rationale while developing an architecture based on them. This report is structured in such a way to mirror the different goals of the thesis. Part 1: Contains a description of the current version of the standard and of other related protocols that collaborate and participate in enhancing security in a typical LAN environment. Part 2: Illustrates the methodology that has been used and the achieved results in order to integrate IEEE 802.1X and an HIPERLAN/2-based network. Part 3: Describes roughly the implementation of the prototype, its limitations and further work to make it usable in a professional and non-experimental environment; furthermore, it describes the result of the testing operation. Part 4: Concludes the report by summarizing the whole work, by illustrating the achieved results and by giving some suggestions for a follow-up of this thesis work.